Implementation and Optimization of Smart Pariri Assistance at the Elementary School Level in West Sumbawa Regency - Abdullah, Abdullah; Suparman, Suparman; Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The limited access to education because of many underprivileged communities has an impact to their children in which they could not obtain such a proper education. The Policy of Pariri Cerdas Assistance Program has been existed as one of the regional government innovations that aimed at achieving equal distribution and expansion of educational access in West Sumbawa Regency. By relatively short period, this policy is considered superficial to discuss. Therefore, the urgency of this research was to focus on the extent of the impact of implementation the Pariri Cerdas Assistance, what factors has been supported and obstructed the implementation of the program, and what were the strategies for optimizing the program of Pariri Cerdas Assistance in West Sumbawa Regency. By applying a qualitative descriptive approach and Field Research, researcher attempted to examine facts in the field that related to the implementation of related policies to research objectivities. The data collection methods applied were observation, interviews and documentation, journal literature, articles and relevant sites to this study. There were 33 samples of informants from 3 zones in the West Sumbawa Regency (North, Central and South Zones). The analysis methods for this research were descriptive and SWOT. According to data analysis, it was concluded that: 1) It is important to identify some supporting and inhibiting factors as part of determining the effective strategy in optimizing Pariri Cerdas Assistance Program, 2) Implementation of Pariri Cerdas assistance is claimed to be quite effective and positive for several aspects, meant that there were still some points to be reinforced involved the factual process and target as evaluation for this program in the future, 3) Grand design strategy for optimizing the program of Pariri Cerdas included; the needs to develop Pariri Cerdas policies, Financing Analysis of Pariri Cerdas program, updating the DTKS as one of references for determining the addressees of Pariri Cerdas regularly, the need to strengthen Mechanism for the next implementation program of Pariri Cerdas, Monitoring and Evaluation of the Pariri Cerdas program, the need of forming such a Task Force Unit which is involving some private sectors and NGOs and supporting the Pariri Cerdas Program, Advocacy for Pariri Cerdas to some parties involved, Digital-Based Innovation in Education Financing Programs, Increasing partnerships to build Innovative breakthroughs in addressing education financing.